GEOMA (GEOMETRI MATEMATIKA) APPLICATION AS GEOGEBRA-BASED LEARNING MEDIA TO TRAIN SPATIAL ABILITY - Siti Mutiah; Mutaqin Anwar; Setiani Yani (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The problem on this research is the low spatial sense ability in geometry material. Students have difficulty transforming literacy into geometric shapes. Thus, it required learning media to support the students in learning the geometry material. This research aims to develop GeoGebra-based mathematics learning media to practice spatial sense ability in geometrical materials for senior high school level practically, effectiveness, and feasibility. This research and development used the ADDIE development model. It covered analyzing needs, designing, developing, implementing the product, and evaluating at each stage. The final result of the development of this learning media is the GEOMA application that has a level of practicality, effectiveness, and feasibility with the category